Firm performance, critical success factors and firm competitiveness of clothing industry in China - Huang, Jing Kai (2022)
The main objective of this study is to determine the relationship between critical success factors and operational performance of clothing manufacturing small and medium enterprises (SMEs) from China. In this study, firm competitiveness is introduced as the mediator between critical success factors and operational performance. This study adopts quantitative research approach by sending out questionnaires and collect primary data from target firms. For the data analysis, this study conducted structural equation modeling (SEM) analysis through SmartPLS. The data analysis examines the relationship between critical success factors (organizational factors, team factors, communication factors, production factors) and operational performance through firm competitiveness which is the mediator in the theoretical framework. The finding of data analysis indicates that there are strong and positive mediating effect from organizational factors, team factors, and production factors towards operational performance through the mediator of firm competitiveness. While there is partial mediating effect between production factors and operational performance through firm competitiveness. Moreover, firm competitiveness has strong and positive effect towards operational performance. In the last part of this study, discussed about the theoretical and practical implications of this study, discussed on how this mechanism will help clothing SMEs from China to improve firm competitiveness and firm’s operational performance.